The development of numerical mapping in preschool children - Jun Zhu; Huanyu Yang; Liangzhi Jia; Chenli Li; Qiang Wu; Yajie Bi; Fangwen Yu; Yun Pan (PLoS ONE, 2025)
The developmental order of numerical mapping and the symmetry of the mapping direction in preschool children remain controversial. In light of this context, this study investigated the developmental characteristics of numerical mapping among preschool children in China. In Experiment 1, 128 children aged 2–4 years were recruited to participate in six numerical mapping tasks with small and large numbers. The results showed no reliable differences between the mapping directions. Notably, the developmental orders of small- and large-number mapping differed, potentially confirming two systems of number representation. Furthermore, previous studies have found that counting or not could affect children’s performance on numerical tasks. Therefore, in Experiment 2, we introduced the condition of “reminding children to count” and recruited 97 children aged 3–4 years to explore its influence on numerical mapping. Our findings revealed that reminding children to count could improve their performance on numerical mappings, resulting in alterations in the symmetry of the mapping direction and developmental order of mapping paths. In conclusion, number size and counting reminders would affect researchers’ assessments of the developmental order of numerical mapping in preschool children, which serves as a guide for nurturing and evaluating the numerical mapping ability of preschool children.